New species of flea of the genus Dactylopsylla Jordan (Insecta: Siphonaptera) from the Flora and Fauna Protection Area Médanos de Samalayuca, Chihuahua, Mexico - Guerra-Murcia, Natalia; Acosta, Roxana; Gatica-Colima, Ana; Vital-García, Cuauhcihuatl; Rueda-Torres, Rolando (Zootaxa, 2021)
A new species of Dactylopsylla Jordan, parasites of Geomyidae rodents from Chihuahua, is described and illustrated as D. samalayucae n. sp. This species is compared with their morphologically closest relatives. Males are characterized by the shape of the upper lobe of the inmovable and movable process, the shape and chaetotaxy of the distal arm of sternum IX and the shape of the crochet; and females by the contour of the distal margin of sternum VII. The geographical distribution of Dactylopsylla is extended to the Chihuahuan desert in Mexico as D. samalayucae n. sp. is reported from south of the Natural Protected Area Médanos de Samalayuca (MS). A recent key to Dactylopsylla species is updated with inclusion of the new species.